If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-3(3a+2)=-5a+7
We simplify the equation to the form, which is simple to understand
-3(3a+2)=-5a+7
Reorder the terms in parentheses
+(-9a-6)=-5a+7
Remove unnecessary parentheses
-9a-6=-5a+7
We move all terms containing a to the left and all other terms to the right.
-9a+5a=+7+6
We simplify left and right side of the equation.
-4a=+13
We divide both sides of the equation by -4 to get a.
a=-3.25
| -6b=55.2 | | 15+5y=-19 | | -16t^2+16t+5=0 | | 14.00*1.00x=35 | | 8t-30=4t+6 | | 5z+3z=56 | | 6r^2+28r=-16 | | 14.00*1.00x=105 | | 8g-3=25 | | 5(4x-7)-(3x-1)2= | | i=400*.12*2 | | 6n^2+22n=8 | | p=2*28+2*70 | | .1x-2.5+2=50 | | f+30=72 | | 8x^2+72= | | 3(m+3)=33 | | 7n^2+45n=28 | | 5a(a+3)-a=-(4a-6)+1 | | 4=8y+5x | | 3x^2+8=-25x | | 10=-2(x-2)+6(x+1) | | 3.5x+7=7 | | 18-7y=-11 | | 2x^2+17x+8= | | -5(4b+2)+(21b-3)=0 | | 2x+x+2x+x=750 | | 20.3=t-(-3.9) | | 3(2t+5)+20= | | 5a(a+3)-a=4a-6+1 | | 40m^2-224=248m | | x+17+x+19-x=602 |